2015
DOI: 10.11622/smedj.2015064
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of solitary intraosseous haemangioma of the femoral neck

Abstract: Intraosseous haemangiomas (IOHs) are benign vascular bone tumours that account for 1% of all primary bone tumours. They are most frequently seen in the vertebrae and skull, and are rarely found in long bones. Herein, we present an uncommon case of a 25-year-old woman with a solitary IOH that occupied the left femoral neck. We describe the clinical, radiological and histological details of the case, as well as the three-year outcome of the surgical treatment, which successfully preserved the femoral head. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The term "aggressive" refers to the presence of radiological features such as extension beyond the vertebral body, destruction of the cortex, and invasion of the epidural and paravertebral spaces. [6,8,14] Based on the radiological features, a vertebral hemangioma can be classified as typical, atypical, or aggressive. [14] In cases of compressive vertebral hemangiomas, the clinical and radiological classifications typically match because of the associations between compressive symptoms and aggressive behavior.…”
Section: Biopsymentioning
confidence: 99%
See 2 more Smart Citations
“…The term "aggressive" refers to the presence of radiological features such as extension beyond the vertebral body, destruction of the cortex, and invasion of the epidural and paravertebral spaces. [6,8,14] Based on the radiological features, a vertebral hemangioma can be classified as typical, atypical, or aggressive. [14] In cases of compressive vertebral hemangiomas, the clinical and radiological classifications typically match because of the associations between compressive symptoms and aggressive behavior.…”
Section: Biopsymentioning
confidence: 99%
“…No recurrence was observed at 39 months of follow-up. [6] Lucia et al reported a cavernous hemangioma of the proximal femur in a young male who received en bloc resection of a tumor due to the large range of involvement and high risk of pathologic fracture. [29]…”
Section: Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological presentations of hemangiomas in the long bones are highly variable and non-specific and are difficult for a correct diagnosis [ 4 ] because diverse matrix found in the bone hemangioma like vessels, fat, fibrous tissue, smooth muscles, and clotted blood may all account for the variable radiological presentations [ 13 , 14 ]. The medullary type mainly occurred at the diaphysis or metaphysis with few involvement of the epiphysis.…”
Section: Discussionmentioning
confidence: 99%
“…CT appearance of hemangioma in long bones correspond to that on radiographs as a lytic lesion with internal trabecula [ 14 ], and in some patients, the thickened vertical trabecular may have a ‘polka dot’ appearance as in the spinal variety [ 13 , 14 ]. On MRI, the long bone hemangioma may demonstrate low, intermediate or high signal intensity on T1WI.…”
Section: Discussionmentioning
confidence: 99%